(untitled) (Research, Society and Development, 2020)
The objective of this article is to describe the first record of a theropod carnivorous dinosaur from the Late Cretaceous of the Adamantina Formation (Bauru Group, Paraná Basin) in the south of the state of Goiás in the Midwest region of Brazil. The methodology of this work was based on a bibliographic survey about the characteristics of teeth of theropods and the geology of the region, in addition to the description and morphological comparisons. This specimen was found in a geodiversity site called Serra da Portaria, in the Paraúna State Park, municipality of Paraúna, where residuals from the Adamantina Formation is exposed. The specimen, a fragmentary tooth covered with iron oxide, but with a partially preserved crown, was assigned as a percentage to an undetermined theropod for having a labiolingually compressed crown and cross section. In addition to the Bauru Group in the state of Goiás, only remnants of sauropod herbivorous dinosaurs are known for the Adamantina and Marília formations, the tooth described here is the first osteological record of a theropod from the south of Goiás.